2011
DOI: 10.1007/s00595-010-4357-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prophylactic treatment with selective serotonin reuptake inhibitors for depression after open-heart surgery

Abstract: The quality of life of patients with depression after open-heart surgery is poor. The early administration of prophylactic medication is therefore necessary for those patients at risk for developing depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…A recent study suggests that antidepressant use may help protect cardiac patients against cardiac related death while in the hospital (Hata et al, 2011). However, several limitations of the study are worth noting: specifically, the sample size was small, patients were not randomized to the antidepressant treatment, and it was not placebo-controlled.…”
Section: Cardiac Eventsmentioning
confidence: 99%
“…A recent study suggests that antidepressant use may help protect cardiac patients against cardiac related death while in the hospital (Hata et al, 2011). However, several limitations of the study are worth noting: specifically, the sample size was small, patients were not randomized to the antidepressant treatment, and it was not placebo-controlled.…”
Section: Cardiac Eventsmentioning
confidence: 99%
“…Ten studies were identified by systematic search to fulfil the inclusion criteria (Table 1) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…All ten studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) reported the outcomes of either 30-day hospital or all-cause mortality, or long-term survival. Two studies (15,23) reported higher mortality in the SSRI group.…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations